Preventing Ischemic Cerebrovascular Events in High-Risk Patients With Non-disabling Ischemic Cerebrovascular Events Using Remote Ischemic Conditioning: A Single-Arm Study - Liu, Shimeng; Gao, Zongen; Meng, Ran; Song, Haiqing; Tang, Tianping; Zhao, Ya; Chen, Rong; Sheng, Yanzhen; Fan, Qianqian; Jiang, Fang; Zhang, Qian; Ding, Jianping; et al. (Frontiers in Neurology, 2021)
Background: Secondary prevention after a high-risk, non-disabling ischemic cerebrovascular event needs to be enhanced. The study was conducted to investigate whether remote ischemic conditioning (RIC) is effective in preventing recurrent events within 3 months in such patients. Methods: This was a four-center, single-arm, open-label Phase IIa futility trial (PICNIC-One Study). Adult patients (≥18 years of age) who had an acute ischemic stroke (AIS) with a National Institutes of Health Stroke Scale score ≤ 3 or a transient ischemic attack (TIA) with moderate-to-high risk of stroke recurrence (ABCD score ≥ 4) within 14 days of symptom onset were recruited. Patients received RIC as adjunctive therapy to secondary stroke prevention regimen. RIC consisted of five cycles of 5-minute inflation (200 mmHg) and 5-minute deflation of cuffs (45 minutes) on bilateral upper limbs twice a day for 90 days. Results: A total of 285 patients met the study criteria, of which 167 provided signed informed consent and were enrolled. Data from 162 were analyzed, whereas five subjects were excluded. Recurrent AIS/TIA occurred in 6/162 (3.7%) patients within 3 months, with no occurrence of hemorrhagic stroke. The top three adverse events were upper limb pain (44/162, 27.2%), petechia (26/162, 16.0%), and heart palpitation (5/162, 3.1%). Sixty-eight (42.0%) subjects completed ≥ 50% of 45-minute RIC sessions. Conclusions: Remote ischemic conditioning is a safe procedure with potential benefit in reducing cerebrovascular events; however, patient compliance to long-term daily RIC needs improvement. Our study provided critical preliminary data to plan a Phase II study.